2020
DOI: 10.3390/nano10112286
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Strategies for the Synthesis of N-Doped Graphene-Like Materials

Abstract: Methods for synthesizing nitrogen-doped graphene-like materials have attracted significant attention among the scientific community because of the possible applications of such materials in electrochemical devices such as fuel cells, supercapacitors and batteries, as well as nanoelectronics and sensors. The aim of this paper is to review recent advances in this scientific niche. The most common synthesis technique is nitridization of as-deposited graphene or graphene-containing carbon mesh using a non-equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…The amorphous phase will deposit, especially at elevated pressures, but will be effectively removed by weak bombardment with positive ions and chemical interaction with reactive neutral species such as H and/or O atoms. Some authors also performed the synthesis of CNWs in nitrogen or ammonia plasma to allow for the doping of CNWs with nitrogen atoms and thus affecting their electronic properties [8]. This was also one of the reasons for choosing polymers such as PA6 and ABS in this investigation, because they contain nitrogen.…”
Section: Influence Of the Processing Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…The amorphous phase will deposit, especially at elevated pressures, but will be effectively removed by weak bombardment with positive ions and chemical interaction with reactive neutral species such as H and/or O atoms. Some authors also performed the synthesis of CNWs in nitrogen or ammonia plasma to allow for the doping of CNWs with nitrogen atoms and thus affecting their electronic properties [8]. This was also one of the reasons for choosing polymers such as PA6 and ABS in this investigation, because they contain nitrogen.…”
Section: Influence Of the Processing Gasmentioning
confidence: 99%
“…These techniques usually require a long deposition time of minutes or even hours. The current progress in the synthesis of carbon nanowalls has been reviewed in the papers [7,8]. Recently, we have shown that nitrogen-containing carbon nanomesh can be deposited in nitrogen plasma using polymer polyethylene terephthalate as the source of a carbon precursor [9].…”
Section: Introductionmentioning
confidence: 99%
“…This indicates most of the CO bonds have disappeared and the maximum number of CN bonds were created. [62] The successful incorporation of nitrogen as well as the nitrogen species conversion that occurs during carbonization in the HCNB was investigated by the high-resolution N 1s XPS spectra (Figure 3c). As shown in Figure 3c, the RGO-700 has no signal due to the absence of nitrogen species.…”
Section: Bonding Feature Analysismentioning
confidence: 99%
“…All the graphenic materials can be doped in an easy, tunable way, thus being suitable for energy storage applications [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%